In vivo anti-nociceptive and anti-inflammatory activities of the aqueous extract of the leaves of Piper sarmentosum. - Zakaria, Zainul Amiruddin; Patahuddin, H.; Tengku Mohamad, Tengku Azam Shah; Israf Ali, Daud Ahmad; Sulaiman, Mohd Roslan (Elsevier, 2010)
Ethnopharmacological relevance: Piper sarmentosum (Piperaceae) is a medicinal plant traditionally used by the Malays to treat headaches, toothaches, coughs, asthma and fever.